The challenge of implementing integrated environmental management within an organisation structure: the case of the environmental section at Drakenstein Municipality - Ahmed, Aalia (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPA)--Stellenbosch University, 2016.